Tinjauan Yuridis Pembuktian Tindak Pidana Pencabulan Dan Persetubuhan Anak Di Bawah Umur Terhadap Pertimbangan Hakim Dalam Putusan Bebas (Postulat, 2026)
This study examines the challenges of proving cases of sexual violence against children, particularly molestation and intercourse, within the Indonesian criminal justice system. Despite being serious crimes with significant impacts on victims and society, many cases result in acquittals not because the crime did not occur, but due to the failure to meet formal evidentiary requirements under the Criminal Procedure Code (KUHAP). This research uses a normative juridical approach with a qualitative method to analyze the evidentiary system and its implications for judicial decision-making. The findings reveal that the rigid application of the minimum two pieces of evidence rule and the unus testis nullus testis doctrine creates major obstacles, especially when the child victim is the only witness. Testimonies given without oath are often reduced to circumstantial evidence, making it difficult for prosecutors to meet the burden of proof. As a result, judges, bound by legal positivism and Article 183 of the KUHAP, tend to issue acquittals. This situation indicates that such decisions reflect systemic weaknesses in procedural law rather than the absence of material truth, highlighting the need for reform in evidentiary rules to better accommodate the nature of child sexual violence cases.